2005
DOI: 10.1074/jbc.m413919200
|View full text |Cite
|
Sign up to set email alerts
|

Epigen, the Last Ligand of ErbB Receptors, Reveals Intricate Relationships between Affinity and Mitogenicity

Abstract: Four ErbB receptors and multiple growth factors sharing an epidermal growth factor (EGF) motif underlie transmembrane signaling by the ErbB family in development and cancer. Unlike other ErbB proteins, ErbB-2 binds no known EGF-like ligand. To address the existence of a direct ligand for ErbB-2, we applied algorithms based on genomic and cDNA structures to search sequence data bases. These searches reidentified all known EGF-like growth factors including Epigen (EPG), the least characterized ligand, but failed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
73
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 43 publications
4
73
0
Order By: Relevance
“…The earliest change in gene expression in the back skin of Fa2h Ϫ/Ϫ mice was the strong up-regulation of Epgn in the basal layer of the SG and in some adjacent cells of the ORS. Epgn is a low affinity EGF receptor/ErbB1 ligand but has high mitogenic activity because of its weak ability to induce ErbB receptor degradation (52). Dahlhoff et al (31) demonstrated a specific SG enlargement in Epgn-transgenic mice.…”
Section: Discussionmentioning
confidence: 99%
“…The earliest change in gene expression in the back skin of Fa2h Ϫ/Ϫ mice was the strong up-regulation of Epgn in the basal layer of the SG and in some adjacent cells of the ORS. Epgn is a low affinity EGF receptor/ErbB1 ligand but has high mitogenic activity because of its weak ability to induce ErbB receptor degradation (52). Dahlhoff et al (31) demonstrated a specific SG enlargement in Epgn-transgenic mice.…”
Section: Discussionmentioning
confidence: 99%
“…Also on chromosome 4, EPGN, EREG, and AREG encode epithelial growth factor (EGF)-like mitogens that stimulate MAP kinase signaling (Kochupurakkal et al 2005). Within the induced cluster on chromosome 1, two ephrin genes, EFNA4 and EFNA3, are AR-regulated.…”
Section: Primary Arg Clustersmentioning
confidence: 99%
“…EGFR is a transmembrane glycoprotein with intrinsic tyrosine kinase activity that becomes activated after binding EGF family members, including EGF, heparin-binding EGF-like growth factor (HB-EGF), amphiregulin (AR), betacellulin (BTC), transforming growth factor-α (TGF-α), epiregulin (EPR) and epigen (Iwamoto and Mekada, 2006;Kochupurakkal et al, 2005). Osteoblast proliferation and differentiation are abnormal in mice lacking EGFR, and this leads to impaired bone formation and skeletal structure (Sibilia et al, 2003;Wang et al, 2004).…”
Section: Introductionmentioning
confidence: 99%